Magnesium Ascorbyl Phosphate Regulates the Expression of Inflammatory Biomarkers in Cultured Sebocytes - Lee, Weon Ju; Kim, Sang Lim; Choe, Yoon Seok; Jang, Yong Hyun; Lee, Seok-Jong; Kim, Do Won (Annals of dermatology, 2015)
Acne is an inflammatory skin disorder caused by inflammatory biomarkers. Magnesium ascorbyl phosphate (MAP) is a stable precursor of vitamin C. It achieves a constant delivery of vitamin C into the skin and has antioxidative effects. We performed this study to evaluate the effect of MAP on the expression of inflammatory biomarkers in cultured sebocytes. Reverse transcription-polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay were performed for inflammatory cytokines and matrix metalloproteinases (MMPs) before and after treatment of cultured sebocytes with MAP (10(-2) M), lipopolysaccharide (LPS) (5 µg/ml) and a combination of MAP and LPS. RT-PCR and western blotting were also performed for antimicrobial peptides (AMPs) and Toll-like receptor (TLR)-4 before and after treatment of cultured sebocytes with MAP, LPS, and a combination of MAP and LPS. Quantification of lipid peroxidation was also conducted. The increased expression of inflammatory cytokines after treatment of cultured sebocytes with LPS was decreased after treatment with MAP. MMPs, AMPs, and TLR-4 were decreased after treatment of cultured sebocytes with MAP and a combination of MAP and LPS, and increased after treatment of cultured sebocytes with LPS alone. Lipid peroxidation was significantly decreased after treatment of cultured sebocytes with MAP and a combination of MAP and LPS. MAP decreased the increased lipid peroxidation after treatment of cultured sebocytes with LPS. MAP may be an effective alternative agent to improve inflammatory reactions in acne.